PENGARUH UKURAN PERUSAHAAN, UKURAN KAP, DAN KUALITAS AUDIT TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN SEKTOR KESEHATAN - Daffa Bagaskara; Petrol; Hera (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Audit report lag is the time it takes to complete an audit and publish financial reports. The importance of issuing audit reports at the right time has led to numerous studies exploring the factors that affect audit report lag. The purpose of this study was to examine the effect of company size, KAP size, and audit quality on audit report lag in health sector companies. The population that is the object of this research is health sector companies listed on the Indonesia Stock Exchange (IDX) in 2018 - 2020. The total population was 60 companies, this research was obtained using purposive sampling technique which then resulted in 15 research samples. for further investigation. The analysis technique used is multiple linear analysis. Based on data analysis and discussion, it can be concluded that Company Size, KAP Size, and Audit Quality have an effect on Audit report lag. The results showed that company size and KAP size had an influence on audit report lag, while audit quality had no effect. The simultaneous results of the results of this study indicate that there is an influence between company size, KAP size, and audit quality on audit report lag.